2017
DOI: 10.1515/bot-2016-0103
|View full text |Cite
|
Sign up to set email alerts
|

Implications of rising temperatures for gametophyte performance of two kelp species from Arctic waters

Abstract: The aim of this study was to determine the temperature effects on photosynthesis, growth and reproduction in gametophytes of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…At 15 °C, gametogenesis of A. esculenta was extremely limited and no sporophytes developed up to 64 days of cultivation. These results are consistent with a study on A. esculenta from Kongsfjorden performed by Park et al (2017) who showed that more sporophytes were produced at 5 °C than at 10 °C and no sporophytes developed at 15 °C in 24 days of cultivation. Not only was sporophyte development faster in our study, but sporophyte growth of A. esculenta was also 2-3 times higher than growth of L. digitata at 4° and 10 °C.…”
Section: Temperature Effects On Different Ontogenetic Processes Of Asupporting
confidence: 93%
“…At 15 °C, gametogenesis of A. esculenta was extremely limited and no sporophytes developed up to 64 days of cultivation. These results are consistent with a study on A. esculenta from Kongsfjorden performed by Park et al (2017) who showed that more sporophytes were produced at 5 °C than at 10 °C and no sporophytes developed at 15 °C in 24 days of cultivation. Not only was sporophyte development faster in our study, but sporophyte growth of A. esculenta was also 2-3 times higher than growth of L. digitata at 4° and 10 °C.…”
Section: Temperature Effects On Different Ontogenetic Processes Of Asupporting
confidence: 93%
“…In addition, the over-represented GO term "generation of precursor metabolites and energy" suggest that female gametophyte cells are actively investing in cell growth and energy production. This is consistent with observational microscopy studies, as female gametophyte cells tend to grow in size while male gametophyte cells tend to grow in number (Lüning, 1980;Destombe and Oppliger, 2011;Park et al, 2017). This investment in cell growth might be advantageous for later sporophyte growth as larger female gametophyte cells will release bigger eggs that tend to generate larger sporophytes (Bell, 1997).…”
Section: Sex-biased Gene Expression Underlies Gender-specific Metabolsupporting
confidence: 82%
“…The temperature range for kelp gametophyte growth and reproduction is species-specific and the width ranges between 5 and 19˚C within the genera Laminaria and Saccharina [25]. In general, seawater temperatures above the broad temperature optimum impair the vegetative growth of gametophytes and their fertilisation success (e.g., [29,46]). The upper lethal temperature limits after long-term exposure to static temperatures (2 wks exposure) are well known for several selected strains of Atlantic Laminaria species [27,47,48].…”
Section: Discussionmentioning
confidence: 99%